2020
DOI: 10.1186/s12936-020-3132-0
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale field trial of attractive toxic sugar baits (ATSB) for the control of malaria vector mosquitoes in Mali, West Africa

Abstract: Background: The aim of this field trial was to evaluate the efficacy of attractive toxic sugar baits (ATSB) in Mali, where sustained malaria transmission occurs despite the use of long-lasting insecticidal nets (LLINs). ATSB bait stations were deployed in seven of 14 similar study villages, where LLINs were already in widespread use. The combined use of ATSB and LLINs was tested to see if it would substantially reduce parasite transmission by Anopheles gambiae sensu lato beyond use of LLINs alone. Methods: A 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(117 citation statements)
references
References 46 publications
3
98
0
Order By: Relevance
“…Furthermore, we predict more substantial reductions in clinical incidence than obtained from the equilibrium relationships; this is in part due to the bene t from higher levels of pre-existing immunity that we expect to decay over subsequent years if the intervention is maintained. However, the study also showed a lower impact on the HLC endpoint underlying the EIR estimates compared to the CDC trap data used for our dynamic model projections [16] . Figure 5C-D shows the predicted reductions in parasite prevalence and clinical incidence due to ATSB for a range of excess mortality values (on the x-axis) and baseline transmission levels (on the y-axis).…”
Section: Predicted Impact Of Atsbs On Malaria Transmissionmentioning
confidence: 70%
See 3 more Smart Citations
“…Furthermore, we predict more substantial reductions in clinical incidence than obtained from the equilibrium relationships; this is in part due to the bene t from higher levels of pre-existing immunity that we expect to decay over subsequent years if the intervention is maintained. However, the study also showed a lower impact on the HLC endpoint underlying the EIR estimates compared to the CDC trap data used for our dynamic model projections [16] . Figure 5C-D shows the predicted reductions in parasite prevalence and clinical incidence due to ATSB for a range of excess mortality values (on the x-axis) and baseline transmission levels (on the y-axis).…”
Section: Predicted Impact Of Atsbs On Malaria Transmissionmentioning
confidence: 70%
“…A cluster-randomised entomological study [16] was undertaken in 14 villages in southern Mali between April 2016 and December 2017.…”
Section: Impact Of Atsbs On Mosquito Catch Numbers and Eir In Malian mentioning
confidence: 99%
See 2 more Smart Citations
“…In the study site an estimated 85% of exposure to malaria vector bites can be prevented by use of ITNs from 22.00 h to 05.00 h but early evening biting outdoors and sporozoite rates of 3.3%, mean that residents are still exposed to ~ 32 infectious bites per person per year even with high ITN compliance (Sanou A., in prep). Early evening biting outdoors when people are active in the peridomestic environment is common across Africa (46), and highlights the need for vector control tools that can protect outdoors, such as insecticide-treated 'eave ribbons', attractive targeted sugar baits or larval source management (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%